Changes in nutrients and decay rate of Ginkgo biloba leaf litter exposed to elevated O3 concentration in urban area - Fu, Wei; He, Xingyuan; Xu, Sheng; Chen, Wei; Li, Yan; Li, Bo; Su, Lili; Ping, Qin (PeerJ, 2018)
Ground-level ozone (O3) pollution has been widely concerned in the world, particularly in the cities of Asia, including China. Elevated O3 concentrations have potentially influenced growth and nutrient cycling of trees in urban forest. The decomposition characteristics of urban tree litters under O3 exposure are still poorly known. Ginkgo biloba is commonly planted in the cities of northern China and is one of the main tree species in the urban forest of Shenyang, where concentrations of ground-level O3 are very high in summer. Here, we hypothesized that O3 exposure at high concentrations would alter the decomposition rate of urban tree litter. In open-top chambers (OTCs), 5-year-old G. biloba saplings were planted to investigate the impact of elevated O3 concentration (120 ppb) on changes in nutrient contents and decomposition rate of leaf litters. The results showed that elevated O3 concentration significantly increased K content (6.31 ± 0.29 vs 17.93 ± 0.40, P < 0.01) in leaves of G. biloba, significantly decreased the contents of total phenols (2.82 ± 0.93 vs 1.60 ± 0.44, P < 0.05) and soluble sugars (86.51 ± 19.57 vs 53.76 ± 2.40, P < 0.05), but did not significantly alter the contents of C, N, P, lignin and condensed tannins, compared with that in ambient air. Furthermore, percent mass remaining in litterbags after 150 days under ambient air and elevated O3 concentration was 56.0% and 52.8%, respectively. No significant difference between treatments was observed in mass remaining at any sampling date during decomposition. The losses of the nutrients in leaf litters of G. biloba showed significant seasonal differences regardless of O3 treatment. However, we found that elevated O3 concentration slowed down the leaf litter decomposition only at the early decomposition stage, but slightly accelerated the litter decomposition at the late stage (after 120 days). This study provides our understanding of the ecological processes regulating biogeochemical cycles from deciduous tree species in high-O3 urban area.
Keywords: Ginkgo biloba; Litter decomposition; Elevated O3 concentration; Litter quality